A decade of summertime measurements of phytoplankton biomass, productivity and assemblage composition in the Pacific Arctic Region from 2006 to 2016. (April 2019) - Giesbrecht, K.E.; Varela, D.E.; Wiktor, J.; Grebmeier, J.M.; Kelly, B.; Long, J.E.
Abstract: We present phytoplankton and nutrient observations from a period of ten years within five biological 'hotspots' in the Bering and Chukchi Seas, as identified by the Distributed Biological Observatory (DBO). Nitrate (NO3 - ) and total and size-fractionated (< and >5 µm) chlorophyll a (Chl a ) concentrations, and rates of carbon ( ρ C, 'primary productivity') and NO3 - utilization ( ρ NO3 ) were measured throughout the euphotic zone during eight cruises in July 2006, 2008 and yearly from 2011 to 2016. Samples were collected at one station within each of these five hotspots, which were located south of St. Lawrence Island (DBO1), south of the Bering Strait in the Chirikov Basin (DBO2), in the southeastern (DBO3) and northeastern (DBO4) Chukchi Sea, and in Barrow Canyon (DBO5). Nitrate concentrations averaged over the 10 years increased with depth and euphotic-zone integrated values were highest in the Chirikov Basin. Subsurface maxima in Chl a were present at about 30 m depth at most locations during every cruise, although the maximum ρ C and ρ NO3 rates were shallower, within the top 10 m of the water column. The f -ratio (calculated as ρ NO3 / ρ C) averaged for all DBO regions and for the 10-year study-period was 0.41 (± 0.24). Similarly, phytoplankton > 5 µm in size accounted for 65 (± 23) % of total Chl a for all regions over the 10 years. Taxonomic analysis done in 2013 showed that diatoms were the dominant taxa throughout all of the DBO regions, with the exception of areas influenced by low-nutrient waters on the eastern side of the Chukchi shelf near the Alaska coast. These coastal waters were dominated by coccolithophores and small (< 7 μm) flagellates and had much lower Chl a concentrations, ρ C and ρ NO3 than farther west. In addition, the proportion of pennate diatoms to total diatom abundance was found to be elevated relative to centric diatoms when sea-ice was present. Our measurements of phytoplankton biomass and ρ C indicated that the higher abundance of pennate diatoms in the euphotic zone was the result of phytoplankton blooms happening below the ice, rather than pennate diatoms being supplied by a sea-ice diatom bloom. The dynamic nature of the Pacific Arctic Region (PAR) resulted in strong interannual variability within each DBO region for all parameters, with no clear increasing or decreasing trends from 2006 to 2016. Spatial variations were more consistent, with the highest rates of ρ C and ρ NO3 occurring in the nutrient-rich waters of the southeastern Chukchi Sea (away from shore), and decreasing in regions further north as NO3 - concentrations were lower. An east-west gradient in phytoplankton biomass and productivity was also observed in the southeastern Chukchi Sea, which can be attributed to differences in the nutrient content of the water masses along the gradient. This study shows that the observed strong interannual variability in phytoplankton biomass and productivity cannot be attributed to differences in methodology or sampling time. It also highlights the need for better temporal and spatial sampling resolution such that the long-term effects of climate-induced changes can be identified against the backdrop of the naturally-strong interannual variability in the PAR.